Alien invasion - Sule, Hassan; Muhamad Awang, Rita; Omar, Dzolkhifli; Yusuf, Faridah; Gnanasegaram, Manjeri (Universiti Putra Malaysia, 2013)
Invasive alien species (IAS) are organisms accidently or deliberately introduced into a natural environment where they are not normally found. Introduced species threatens the environment, economy, society and human health. Recently, a few IAS were found to threaten the Malaysian fruit and vegetable industries. The Asian citrus psyllid, Diaphorina citri (Hemiptera: Psyllidae), is a sap-sucking pest of limau madu (Citrus sinensis (Linnaeus) Osbeck). Infestation causes defoliation and dieback leading to dwarfing. Diaphorina citri is also a vector for Candidatum liberibacter asiaticus which causes the Citrus Greening Disease. Recently, Tamarixia radiata Waterston (Hymenoptera:Eulophidae) was found parasitizing D. citri nymphs in Malaysia.